ALS-FTLD associated mutations of SQSTM1 impact on Keap1-Nrf2 signalling - Goode, Alice; Rea, Sarah; Sultana, Melanie; Shaw, Barry; Searle, Mark S.; Layfield, Robert (Elsevier, 2016)
The transcription factor Nrf2 and its repressor protein Keap1 play key roles in the regulation of antioxidant stress responses and both Keap1-Nrf2 signalling and oxidative stress have been implicated in the pathogenesis of the ALS-FTLD spectrum of neurodegenerative disorders. The Keap1-binding partner and autophagy receptor SQSTM1/p62 has also recently been linked genetically to ALS-FTLD, with some missense mutations identified in patients mapping within or close to its Keap1-interacting region (KIR, residues 347–352) of SQSTM1/p62. Here we report the effects on protein function of four different disease associated mutations of SQSTM1/p62 which affect the KIR region. Only mutations mapping precisely to the KIR (P348L and G351 A) were associated with a loss of Keap1 binding in co-immunoprecipitations comparable to wild-type SQSTM1/p62. These selective effects on Keap1 recognition were entirely rational based on protein structural models. Consistent with impaired Keap1 binding, the P348L and G351A KIR mutants showed reduced ability to activate Nrf2 signalling compared to wild-type SQSTM1/p62 in antioxidant response element (ARE)-luciferase reporter assays. The results suggest that SQSTM1 mutations within the KIR of SQSTM1/p62 contribute to aetiology of some cases of ALS-FTLD through a mechanism involving aberrant expression or regulation of oxidative response genes.